米曲霉发酵对棉籽壳饲用品质的影响米曲霉发酵对棉籽壳饲用品质的影响 - 陈天明1，李新民2，张国玉2，赵海山3，陆健1，蔡国林1 CHEN Tianming1, LI Xinmin2, ZHANG Guoyu2, ZHAO Haishan3, LU Jian1, CAI Guolin1 (Zhongguo youzhi, 2024)
旨在改善棉籽壳的饲用品质，研究了米曲霉TM-1发酵对棉籽壳中棉酚和纤维类物质降解、蛋白质品质提升和有益代谢产物积累的影响。结果显示：米曲霉发酵后棉籽壳中棉酚含量由645.3 mg/kg降低为137.2 mg/kg，降解率达到78.7%；发酵后棉籽壳结构松散，空隙较大，且木质素、纤维素、半纤维素、中性洗涤纤维和酸性洗涤纤维含量均明显下降，表明影响棉籽壳消化利用的结构屏障被有效降解；发酵后棉籽壳中总酸和8种有机酸含量均显著增加，其中苹果酸含量提高了49.2倍，达到734.0 mg/100 g；发酵后棉籽壳中粗蛋白质含量由12.5%增加至15.5%，酸溶蛋白占比由4.8%上升到13.5%，分子质量在1 000 Da以下的寡肽含量占比达83.0%，游离氨基酸总量增加了115.7%，其中限制性氨基酸赖氨酸和组氨酸分别增加了117.4%和64.2%；发酵后棉籽壳具有丰富的水解酶系，包括中性蛋白酶、纤维素酶、β-葡聚糖酶和β-1，4内切木聚糖酶等，其酶活分别为245.2、13.4、39.7、19.7 U/g。综上，经过米曲霉TM-1发酵处理，棉籽壳的饲用品质得到了明显改善。In order to improve the feeding quality of cottonseed shells, the effects of Aspergillus oryzae TM-1 fermentation on the degradation of gossypol and fiber-like substance, the improvement of protein quality and the accumulation of beneficial metabolites in cottonseed shells were studied. The results showed that after fermentation, the gossypol content in cottonseed shells decreased from 645.3 mg/kg to 137.2 mg/kg, and the degradation rate reached 78.7%. The structure of cottonseed shells fermented was loose and the gap was large, and the contents of lignin, cellulose, hemicellulose, neutral detergent fiber and acid detergent fiber decreased significantly, indicating that the structural barrier affecting the digestion and utilization of cottonseed shells was effectively degraded. The contents of total acid and eight organic acids in cottonseed shells increased significantly, and the content of malic acid increased by 492 times, reaching 734.0 mg/100 g. The content of crude protein in cottonseed shells increased from 12.5% to 15.5%, the proportion of acid-soluble protein increased from 4.8% to 13.5%, the content of oligopeptides with molecular weight below 1 000 Da accounted for 83.0%, and the total free amino acids increased by 115.7%. The limiting amino acids lysine and histidine increased by 117.4% and 64.2%, respectively. The fermented cottonseed shells were rich in hydrolytic enzymes, including neutral protease, cellulase, β-glucanase and β-1,4 endoxylanase, and their enzyme activities were 245.2, 13.4, 39.7 U/g and 19.7 U/g, respectively. In summary, the feeding quality of cottonseed shells is significantly improved by Aspergillus oryzae TM-1 fermentation.